Birth asphyxia outcomes and associated factors among newborns admitted to a tertiary hospital in Eastern Uganda: A prospective cohort study - Grace Apio; Scovia Nalugo Mbalinda; Jimmy Patrick Alunyo; Ambrose Okibure; Brian Tonny Makoko; Molly McVoy; Elizabeth Ayebare (BMC Pregnancy and Childbirth)
Abstract Background Birth asphyxia (BA) is a significant global health challenge, contributing to an estimated 23% of neonatal deaths worldwide and a substantial burden of long-term disabilities. It results from interrupted blood flow and gas exchange to the fetus, leading to neuronal injury and short or long-term outcomes. While most affected newborns recover fully, a notable proportion develop hypoxic-ischemic encephalopathy (HIE), associated with high morbidity and mortality. This study aimed to describe Birth asphyxia outcomes and associated factors among newborns admitted at Mbale Regional Referral Hospital (MRRH.) Methodology We conducted a longitudinal prospective study involving mother-baby pairs with birth asphyxia within the first 24 hour (of life admitted to MRRH. Participants were recruited using a consecutive sampling approach. Data was collected using structured questionnaires and analysed with STATA version 15. Logistic regression was employed to determine factors associated with poor outcomes among newborns with birth asphyxia, with results presented as crude and adjusted odds ratios (AOR). Results A total of 286 mother-baby pairs participated in the study. Hypoxic ischemic encephalopathy (HIE) was observed in 70.3% of cases at admission, which decreased to 45.1% at 12 h and 24.6% at 24 h. Mortality rates were 4.6%, 4.4%, and 1.2% at admission, 12 h and 24 h, respectively. Key independent factors associated with severe HIE included referral from lower-level health facilities (AOR 4.2; CI 1.7–10.0; P < 0.001), passage of meconium-stained amniotic fluid (AOR 2.2; CI 1.2–4.1; P = 0.014), and newborn resuscitation (AOR 5.1; CI 1.8–15.0; P = 0.003). Conclusion The incidence of mortality and HIE among asphyxiated newborns remains high. Referral from lower-level health facilities, the passage of meconium-stained amniotic fluid, and the need for newborn resuscitation were significant predictors of severe HIE and mortality. Strengthening maternal and neonatal care at peripheral health facilities and timely referrals could mitigate these outcomes.